2017
DOI: 10.1080/24733938.2017.1330552
|View full text |Cite
|
Sign up to set email alerts
|

Visual function of English Premier League soccer players

Abstract: Purpose: Examine visual function of soccer players of different skill level and playing position. Methods: Elite players from an English Premier League soccer club (n=49) and intermediate players (n=31) completed an assessment on a Nike SPARQ Sensory Station of: static and dynamic visual acuity, contrast sensitivity, accommodative-vergence facility, target capture and perception span. Results: There was no difference between elite and intermediate players for all measures. However, competitive soccer players (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Additionally, shooting success was noted to decrease with reduced visualization of the basket 3 . In soccer, the visual function of English Premier League soccer players was found to be superior to that of normal adults 4 , while the visual tracking ability of Brazilian soccer players was found to be superior in more skilled players as compared to less skilled players 5 . In motorsport, elite academy participants from New Zealand were noted to have superior visual acuity as well as perception time when compared to sex and age-matched controls 6 .…”
Section: Introductionmentioning
confidence: 90%
“…Additionally, shooting success was noted to decrease with reduced visualization of the basket 3 . In soccer, the visual function of English Premier League soccer players was found to be superior to that of normal adults 4 , while the visual tracking ability of Brazilian soccer players was found to be superior in more skilled players as compared to less skilled players 5 . In motorsport, elite academy participants from New Zealand were noted to have superior visual acuity as well as perception time when compared to sex and age-matched controls 6 .…”
Section: Introductionmentioning
confidence: 90%
“…Other studies, with field players, have been focused on young players rather than professional players . Recently, Roberts et al published a study that analysed 49 elite players from an English Premier League, and concluded that the visual function of competitive soccer players is superior to non‐athletic adults, but does not differentiate the elite and intermediate player. The research in these studies was focused on perceptual skills, eye–foot co‐ordination or reaction time instead of visual skills.…”
mentioning
confidence: 99%
“…Based on the results of accommodation facility, previous research by Ghasemi et al (2009), and Jafarzadehpur and Yarigholi (2004) has found similar differences in accommodation facility when comparing experts and novices, albeit in soccer referees and table tennis champions, respectively (10,11). However, Roberts et al (2017) found no difference in accommodation facility when comparing novice and expert soccer players (12). Interestingly, expert athletes, when compared to novices, may have an increased accommodation facility due to having a better developed visual system that allows a quicker and more efficient adjustment of their eyes from a far to a near target (12).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, expert athletes, when compared to novices, may have an increased accommodation facility due to having a better developed visual system that allows a quicker and more efficient adjustment of their eyes from a far to a near target (12). This more efficient adjustment may allow experts to better track objects like a ball in rugby (12).…”
Section: Discussionmentioning
confidence: 99%